Pengaruh Tingkat Keamanan, Kepercayaan, dan Pengalaman Pengguna Layanan Wondr By BNI: Studi Kasus pada Gen Z di Kota Malang - Cindy Permata Dewi; Ajeng Kartika Galuh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the effect of the level of security, trust, and user experience on customer satisfaction of Wondr By BNI users Case Study on Gen Z in Malang City. Using a quantitative approach, data was collected from 100 respondents through questionnaires and analyzed using SEM-PLS analysis. This study aims to analyze the effect of the level of security, trust and user experience of the Wondr By BNI application service on BNI Bank customer satisfaction, especially Gen Z in Malang City. And the results of this study indicate that the variables Security (X1), Trust (X2), User Experience (X3) have a positive and significant effect on customer satisfaction.